PELUANG BISNIS MENJADI KONTEN KREATOR DI KALANGAN PEMUDA DESA BANJAR KEMUNING SEDATI SIDOARJO PADA ERA DIGITAL - Suhartono Suhartono; I Wayan Arsana; Akhmad Qomaru Zaman; Pandu Rudy Widyatama; Elok Kinanti; Eka Safitri Utami; Qurrotul Uyun; Irnawati Irnawati (FKIP Universitas Samawa, 2023)
The digital era is now changing the way people view doing business, especially the millennial generation. This millennial generation is one of the few people affected by technology. This generation is not only surfing social media, but also working on their personal accounts to take advantage of unlimited digital business opportunities, ranging from being speakers, brand ambassadors, endorsements, content creators, and many more. Business opportunities in the digital era are very promising, but often some of the millennial young generation now have not found a direction in building personal branding. This happened because of the lack of understanding and readiness among these young people. The need for real efforts through community service programs carried out by the PPKn Study Program of PGRI Adi Buana University Surabaya to socialize the youth of Banjar Kemuning Village to use social media by becoming content creators. The method of implementing this community service is the preparation, implementation, and evaluation stages. The result of this service program is to open views and provide understanding to village youth to use social media as a business opportunity. The active response and enthusiasm of village youth in paying attention to the material shows interest in becoming content creators.